Wag the dog - Beinhart, Larry 1947- (New Line Cinema, 1997)
When the President of the USA is involved in a sex scandal an adviser joins forces with a Hollywood producer to divert the media spotlight to a war. Lacking a real war they create one.
Keywords: Feature films; Satire; Präsidentenwahl; Film